2021
DOI: 10.3390/jcm10040616
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis on the Effect of Contingency Management for Patients with Both Psychotic Disorders and Substance Use Disorders

Abstract: Background: Substance use disorders (SUD) are highly prevalent among psychotic patients and are associated with poorer clinical and functional outcomes. Effective interventions for this clinical population are scarce and challenging. Contingency management (CM) is one of the most evidence-based treatments for SUD’s, however, a meta-analysis of the effect of CM in patients with a dual diagnosis of psychotic disorder and SUD has not been performed. Methods: We searched PubMed and PsycINFO databases up to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
1
5
1
Order By: Relevance
“…Another possible explanation lies in the investigated patient population. Although a recent meta-analysis performed by our group did find a positive effect of CM in patients with psychosis, the effect size is lower than that reported in general addiction research [20]. Thus, it might be the case that CM is less effective for patients suffering from psychosis.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Another possible explanation lies in the investigated patient population. Although a recent meta-analysis performed by our group did find a positive effect of CM in patients with psychosis, the effect size is lower than that reported in general addiction research [20]. Thus, it might be the case that CM is less effective for patients suffering from psychosis.…”
Section: Discussioncontrasting
confidence: 70%
“…The effect sizes, however, are lower than those generally found in addiction research. In contrast to 2 of 12 general SUD evidence, there was no effect on retention in treatment [20]. These findings are in line with another recent review, showing CM to be efficacious in producing cannabis use reductions and abstinence amongst individuals with a psychotic spectrum or major depressive disorder [21].…”
Section: Introductionsupporting
confidence: 83%
“…According to the AMSTAR 2 ratings of the other three metaanalyses, one was rated "low" quality (Sheridan Rains et al, 2020) because it did not account for risk of bias in individual studies when discussing results, and two were rated "critically low" quality (Destoop et al, 2021;Pfund et al, 2021) because they did not use a comprehensive literature search strategy, account for risk of bias in individual studies when discussing results, and provide a satisfactory explanation for, and discussion of, any heterogeneity in the results. a The designation of the Bolivar and Ginley meta-analyses as low quality is probably an underestimate.…”
Section: Amstar 2 Ratingsmentioning
confidence: 99%
“…Overall, among all patients regardless of their dominant diagnosis, as many as 60% of those with a mood disorder and 80% of those with a schizophrenia-spectrum disorder have been shown to have a comorbid SUD (Swadi and Bobier, 2003). Comorbid substance use is problematic because it is associated with poorer clinical and functional outcomes (Destoop et al, 2021; Suvisaari et al, 2018).…”
mentioning
confidence: 99%
“…Multiple studies document the fact that individuals with mental illnesses and co-occurring SUDs experience significant adverse social determinants of health. Studies have repeatedly shown that such individuals are more likely to experience poverty, homelessness, and unemployment, and are more likely to have criminal justice involvement (Carlsen-Landy et al, 2020; Carrà et al, 2018; Destoop et al, 2021; Eggink et al, 2019; Kovasznay et al, 1997; Manhapra et al, 2021; Seibyl et al, 1993; Soyka et al, 1993; Suvisaari et al, 2018; Swadi and Bobier, 2003). These associations are bidirectional, and causality is often difficult to establish.…”
mentioning
confidence: 99%